Ethyl diazoacetate synthesis in flow - Delville, Mariëlle M. E.; van Hest, Jan C. M.; Rutjes, Floris P. J. T. (Beilstein Journal of Organic Chemistry, 2013)
Ethyl diazoacetate is a versatile compound in organic chemistry and frequently used on lab scale. Its highly explosive nature, however, severely limits its use in industrial processes. The in-line coupling of microreactor synthesis and separation technology enables the synthesis of this compound in an inherently safe manner, thereby making it available on demand in sufficient quantities. Ethyl diazoacetate was prepared in a biphasic mixture comprising an aqueous solution of glycine ethyl ester, sodium nitrite and dichloromethane. Optimization of the reaction was focused on decreasing the residence time with the smallest amount of sodium nitrite possible. With these boundary conditions, a production yield of 20 g EDA day−1 was achieved using a microreactor with an internal volume of 100 μL. Straightforward scale-up or scale-out of microreactor technology renders this method viable for industrial application.
Keywords: diazo compounds; diazotization; ethyl diazoacetate (EDA); flow chemistry; microreactor technology